Client satisfaction and associated factors towards the health service provided to members of a community-based health insurance scheme in Southern Ethiopia - Babore, Getachew Ossabo; Ashine, Taye Mezigebu; Heliso, Asnakech Zekiwos; Habebo, Teshome Tesfaye (Frontiers in Health Services, 2023)
Background Globally, 1.3 billion poor people have no access to health services due to their inability to afford payment when they need services. According to a report published by the WHO in 2014, globally 150 million people are pushed into poverty as a result of direct payment for health services. Objective This study aims to assess the satisfaction level of clients and associated factors toward health services provided to members of a community-based health insurance (CBHI) scheme. Methods An institutional-based cross-sectional study design was employed. A total sample size of 393 people was estimated using a single population formula, and three health facilities (HFs) were selected using a simple random sampling method, whereas study participants were selected by using a systematic sampling method. All patients who visited the HFs were included, whereas women who visited the HFs for maternity service were excluded from the study. A reliability test (Cronbach’s alpha) was performed to determine the internal consistency for these items to measure the satisfaction level of the clients. Epi Info software version 7 was used to calculate the sample size and to enter data, whereas further data cleaning and analysis were conducted using SPSS software version 20. Results A total of 367 clients enrolled in the community-based health insurance scheme were interviewed, showing a response rate of 93%. The reliability test (Cronbach's alpha) value for the items used to measure level of client satisfaction was 0.817. The overall level of the clients’ mean satisfaction toward health service provision was 63.1% (3.95 + 0.47 SD). This study found that age with AOR = 0.11 [95% CI (0.01–0.79)], residence with AOR = 1.80 [95% CI (1.79–3.66)], number of family with AOR = 2.27 [95% CI (1.46–11.22)], frequency of visits to HFs with AOR = 13.62 [95% CI (2.09–88.58)], and clients’ level of knowledge with AOR = 3.33 [95% CI (1.06–10.42) had a statistical significant association with client satisfaction toward health service provision. Conclusion Our study found that the perceived level of client satisfaction is higher than previous studies. Residence, frequency of visits, level of knowledge, payment during referral time, number of family members, and frequency of visits were identified as predictors of client satisfaction on the health service provision.